Analisis Kualitas Butir Soal Instrumen Evaluasi IPA Kelas VIII di SMP Negeri 27 Makassar Menggunakan Teori Tes Klasik dan Rasch Model - Himmatun Nisfirramadhani; Sitti Saenab; Rifda Nur Hikmahwati Arif (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Analysis of the Quality of Grade VIII Science Assessment Items at SMP Negeri 27 Makassar Using Classical Test Theory and the Rasch Model. The quality of assessment instruments is essential for ensuring accurate measurement of students’ learning outcomes. This study aimed to analyze the quality of science achievement test items for Grade VIII students at SMP Negeri 27 Makassar through the integration of Classical Test Theory (CTT) and the Rasch Model. A descriptive quantitative approach was employed using 25 multiple-choice test items administered to 26 students. The CTT analysis included empirical validity, KR-20 reliability, item difficulty, and discrimination index, while the Rasch analysis examined reliability, separation indices, item fit, and the Wright Map. The results showed that 13 items (52%) met the validity criteria, with a KR-20 reliability coefficient of 0.8527, indicating high internal consistency. Most items were classified as having moderate difficulty (60%), and 72% demonstrated good to very good discrimination power. The Rasch analysis yielded a person reliability of 0.8177, an item reliability of 0.7232, and identified 16 items (64%) as fitting the model. The integrated analysis recommended retaining 8 items, revising 13 items, and eliminating 4 items. These findings indicate that integrating CTT and the Rasch Model provides a more comprehensive evaluation of test item quality and supports evidence-based decision-making in educational assessment development.